Computer architectures : constructing the common ground - Vardouli, Theodora; Touloumi, Olga (Milton Park, Abingdon, Oxon : New York, NY : Routledge, 2020)
"Computer Architectures is a collection of multidisciplinary historical works that unearth sites, concepts, and concerns that catalyzed the cross-contamination of computers and architecture in the mid-20th century. Actively constructing the common ground between design and computing, this collection addresses audiences working at the nexus of design, technology, and society, including historians and practitioners of design and architecture, science and technology scholars, and media studies scholars"--
OCLC-licensed vendor bibliographic record.
Keywords: Architectural design -- Data processing; Computer-aided design; Architecture -- Philosophy -- History -- 20th century; ARCHITECTURE / General; ARCHITECTURE / History